Extinct and Vanishing Mammals from the Desert of Rajasthan and the Problem of their Preservation - Prakash, Ishwar (Indian Forester, 1958)
Black buck, gazelle, panther, wild boar were in great numbers in the desert region in the early thirties of this century. Due to abolition of the Princely states, wild life has suffered great extermination. The Indian Wild Life Board and the Forest Department of Rajasthan have plans to open some Zoological parks and Sanctuaries in Ghana, Bharatpur; Siraska, Alwar, Satkari, Dholpur, Dara, Kota and Jaisamand, Udaipur. But no attention is being paid to Western Rajasthan which has certain important wild animals. Suggestions have been made to declare three regions as reserve areas. The paper also lists some animals as have vanished from this region. It also includes reasons for their mass destruction.